Some Aspects of -Units in BCK-Algebras - Hee Sik Kim; J. Neggers; Keum Sook So (Journal of Applied Mathematics)
We explore properties of the set of d-units of a -algebra. A property of interest in the study of -units in -algebras is the weak associative property. It is noted that many other -algebras, especially -algebras, are in fact weakly associative. The existence of -algebras which are not weakly associative is demonstrated. Moreover, the notions of a -integral domain and a left-injectivity are discussed.